Respuesta :

Answer:


Common difference = x - 2.


Step-by-step explanation:


Differences:


-2x - 9 - (-3x - 7)


= -2x - 9 + 3x + 7


= x - 2


-x - 11 - (-2x - 9)


= - x - 11 +2x + 9


= x - 2


So, it is Arithmetic.



Answer:

Arithmetic sequence.

Common difference = -x - 11

Step-by-step explanation:

This is an arithmetic sequence.

-3x - 7, -2x - 9,  -x - 11, ...

Find the common difference.

Common difference =second term - first term.

                                 = -2x - 9 - (-3x - 7)

                                = -2x -  9 + 3x  +7

                                = -2x + 3x - 9 + 7      {Combine like terms}

                                = x - 2

If we add the common difference to the second term, we will get the third term.

Third term = second term + common difference

                  = -2x - 9 + x - 2

                  = -2x + x - 9 - 2

                  = -x - 11.

Hence this is an arithmetic sequence.